Energy and greenhouse gas implications of shared automated electric vehicles. (April 2022) - Saleh, Marc; Milovanoff, Alexandre; Daniel Posen, I.; MacLean, Heather L.; Hatzopoulou, Marianne
Abstract: Automated vehicles can facilitate vehicle sharing within and between households, thus decreasing ownership rates, albeit increasing miles travelled. While electrification can achieve deep reductions in transportation-related greenhouse gas emissions, shared automated electric vehicles will have different charging needs considering their higher mileage. In this study, travel survey data collected in Toronto is used to optimize the charging needs of shared automated electric vehicles, with the objective of reducing greenhouse gas emissions from electricity generation by choosing charging times that are associated with lower marginal emission factors. Optimized charging schedules reduce greenhouse gas emissions by at least 50% relative to vehicles charging once they return home. Life cycle assessment of multiple sharing scenarios indicates that higher levels of sharing increase emissions. Indeed, empty mileage associated with vehicle relocation and higher deterioration lead to a higher fleet turnover. With vehicle sharing, there is a risk of increasing mileage and vehicle production emissions.